INTERSECTION OF SHARIA ECONOMIC LAW IN ASIAN RELIGIOUS COURTS (A Case Study of Indonesia) - Akbar Ryant Prabowo, Ilham (Universitas Muhammadiyah Surabaya, 2024)
This research delves into the competency of religious courts within the framework of Sharia economic law, specifically focusing on a case study of religious courts in Indonesia. These courts hold a crucial role in resolving disputes related to Sharia economics, including matters of marriage, inheritance, and family finance. The competency of these courts, which involves a deep understanding of Sharia economic principles such as inheritance law, transactions (muamalah), and Sharia financial contracts, is vital for dispensing justice in line with Sharia principles. The study scrutinizes the ability of Indonesian religious courts to apply and comprehend Sharia economic law in their legal proceedings. This research offers insights into the nuanced aspects of religious court competency through a qualitative approach, employing methods such as case studies and content analysis. By focusing on qualitative methods, the study provides a rich and in-depth understanding of how religious courts navigate and interpret Sharia economic law within the Indonesian context. This research contributes significantly to the understanding of the importance of religious court competency in supporting Sharia economics in Indonesia and offers valuable insights for policymakers and practitioners.